2022
DOI: 10.3390/ma15030982
|View full text |Cite
|
Sign up to set email alerts
|

Histological Processing of CAD/CAM Titanium Scaffold after Long-Term Failure in Cranioplasty

Abstract: Cranioplasty is a frequently performed procedure after craniectomy and includes several techniques with different materials. Due to high overall complication rates, alloplastic implants are removed in many cases. Lack of implant material osseointegration is often assumed as a reason for failure, but no study has proven this in cranioplasty. This study histologically evaluates the osteointegration of a computer-aided design and computer-aided manufacturing (CAD/CAM) titanium scaffold with an open mesh structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The use of titanium cranioplasty is now accepted as an alternative with high biocompatibility, mechanical strength, and infection resistance, which integrates with the bone and provides favorable cosmesis. With advances in 3D printing technologies, the biomechanical properties of the titanium material can be adjusted by altering the surface morphology, such as porosity and pore size, to improve osseointegration between the bone and the implant 15,16 . Compared with the titanium mesh that has been widely inspected in previous studies, few studies have reported experiences regarding the use of 3D-printed material in cranioplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of titanium cranioplasty is now accepted as an alternative with high biocompatibility, mechanical strength, and infection resistance, which integrates with the bone and provides favorable cosmesis. With advances in 3D printing technologies, the biomechanical properties of the titanium material can be adjusted by altering the surface morphology, such as porosity and pore size, to improve osseointegration between the bone and the implant 15,16 . Compared with the titanium mesh that has been widely inspected in previous studies, few studies have reported experiences regarding the use of 3D-printed material in cranioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in 3D printing technologies, the biomechanical properties of the titanium material can be adjusted by altering the surface morphology, such as porosity and pore size, to improve osseointegration between the bone and the implant. 15,16 Compared with the titanium mesh that has been widely inspected in previous studies, few studies have reported experiences regarding the use of 3D-printed material in cranioplasty. Our primary concern was the introduction of a new biomaterial, the SLM-produced titanium alloy scaffold, and its suitability for various clinical applications.…”
Section: Discussionmentioning
confidence: 99%